Women and Reproductive Technologies The Socio-Economic Development of Technologies Changing the World - Burfoot, Annette (Routledge Research in Gender and Society, 2022)
A sociological and historical study of the development of reproductive technologies, this book focuses on key technological developments through a biomedicalization lens with special attention to gender. Using in vitro fertilization (IVF) as a hub, it critically examines the main areas of related socio-technical developments: reproductive science, birth control, animal husbandry, genetics and reproductive medicine. Employing a critical framework to illuminate dominant discourses, the book also highlights examples of social resistance, as well as contradictory responses to new reproductive technologies. Over eight chapters, the author examines the social history of reproduction and sexuality, reproductive technologies from old to new and debates surrounding new reproductive technologies and genetic engineering. Women and Reproductive Technologies pays close attention to the interconnections between the business of reproduction (and replication industries), the sociality of reproduction (including reproductive justice) and what are considered the technologies themselves. As such, it constitutes essential reading for students and researchers in the fields of sociology, health studies and gender studies interested in the current state of human reproduction.